Psychometric properties of the Pandemic-Related Pregnancy Stress Scale (PREPS) - Heidi Preis; Brittain Mahaffey; Marci Lobel (Taylor & Francis Group, 2020)
Purpose Pregnant women are facing numerous COVID-19 related burdens including social isolation, financial insecurity, uncertainty about the impact of the virus on fetal development, and prenatal care restrictions. We tested the psychometric properties of a new instrument designed to assess the extent and types of pandemic-related stress experienced by pregnant women. Materials and methods 4,451 pregnant women from across the U.S. were recruited via social media and completed an online questionnaire in April-May 2020. The questionnaire included measures of psychological, sociodemographic, and obstetric factors and the new Pandemic-Related Pregnancy Stress Scale (PREPS). Results Confirmatory factor analyses of the PREPS showed excellent model fit. Three factors - Perinatal Infection Stress (5 items), Preparedness Stress (7 items), and Positive Appraisal (3 items) - converged and diverged with expected psychological factors, and scales created from these factors demonstrated acceptable to good reliability (α's 0.68-0.86). In addition, mean PREPS scores were associated with perceived risk of infection, and with financial and vocational COVID-19 related burdens. Conclusion The PREPS is a robust instrument to assess multidimensional COVID-19 pandemic prenatal stress. It is a valuable tool for future research to examine vulnerability to pandemic stress and how this stress may affect women and their offspring.